Water Footprint of Milk Production in Andhra Pradesh - devi, rapolu harika (Indian Journal of Dairy Science, 2015)
Highly populous India has huge economy and a remarkable economic growth in the last decade. With the booming economy, people’s income, expenditure patterns and their lifestyles are changing. Rapid urbanization is also adding fuel to these changes. As a result, food consumption patterns are changing, more towards high income elastic milk, which demands more feed grains and in turn more water resources. This requires better quantification and analysis of nexus between water with milk production which is important for nutritional and livelihood security of Bharat (rural India). Quantification can be done by Water Footprint concept. The average water footprint of milk production in Andhra Pradesh for Crossbred cow, buffalo and local cow is 10.50, 6.73 and 2.01 m3/ lactating animal. It is correlated with feed requirements of animal, feeding pattern and water footprint of crops fed. Water consumption for it can be reduced by increasing crop and milk productivities.